2022
DOI: 10.1037/edu0000674
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating calibration: A meta-analysis of learning strategy instruction interventions to improve metacognitive monitoring accuracy.

Abstract: Monitoring, a regulation of cognition component of metacognition, is an essential aspect of self-regulated learning. Monitoring is recognized as learners' ability to successfully understand what they are learning, and typically involves metacognitive activities such as questioning, reflection, drawing inferences, and self-generating feedback. However, while extant research converges on the notion that monitoring is a malleable and trainable skill, no investigation to date has systematically explored difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 76 publications
(194 reference statements)
0
10
0
1
Order By: Relevance
“…Both self-knowledge and contextual knowledge are constantly monitored and provide cues for the subsequent self-regulation of the creative process (Zielińska, Lebuda et al, 2021;2022).…”
Section: Do We Need Metacognition For Creativity? a Necessary Conditi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Both self-knowledge and contextual knowledge are constantly monitored and provide cues for the subsequent self-regulation of the creative process (Zielińska, Lebuda et al, 2021;2022).…”
Section: Do We Need Metacognition For Creativity? a Necessary Conditi...mentioning
confidence: 99%
“…The higher-order thinking has long been a topic of discussion in philosophy because of its' perplexing nature (Rosenthal, 1993;White, 1988). As a practical consequence, the creativity research shows only a small correlation between offline measures of creative metacognition and actual creative performance (Mevarech & Paz-Baruch, 2022; Urban & Urban, in preparation; Zielińska, Forthmann et al;2022). As Snyder et al (2019) point out in their systematic review, the ever-increasing use of self-reported questionnaires in creativity research may be therefore problematic (see also Craig et al, 2020, for a systematic review on the use of self-report questionnaires in metacognition research).…”
Section: Off-line Measures Of Creative Metacognition: Self-reported Q...mentioning
confidence: 99%
“…At the same time, monitoring and evaluating strategies are also crucial for a successful learning experience, thus attracting much attention from scholars. Past research elucidated that learners’ monitoring accuracy can significantly influence overall test performance ( Thiede et al, 2003 ), while monitoring accuracy can also be improved through learning strategy instruction intervention ( Gutierrez de Blume, 2022 ). After a test, learners can also apply evaluation techniques to reflect upon the effectiveness of the strategies used when preparing or during the test ( Stanton et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the second step, the accuracy of creative metacognitive monitoring is calculated. At the time of writing, two well-established accuracy indices have been adapted from the metacognition research in other domains (see Schraw, 2009a, 2009b for a conceptualization of accuracy indices suited to different kinds of judgments and variable types; and de Blume, 2022 for a meta-analysis on how different judgments and accuracy indices influence the obtained effect sizes). Rominger et al (2022) employed an absolute accuracy index that indicates the absolute magnitude of an individual’s monitoring accuracy.…”
Section: Creative Metacognition (Cmc)mentioning
confidence: 99%